USE OF ONTOLOGIES ON INFORMATION RETRIEVAL: Main approaches, problems and proposals for improvements - Reis, Marcia Cristina dos [UNESP]; Ferneda, Edberto [UNESP] (My University, 2021)
The ontologies are being used to implement new features and improvements in information search and retrieval systems, especially in web context. This article aims to present an overview of ontologies in information retrieval systems use, discussing types of applications, application areas, main approaches, proposals for improvements, validated studies by users and still researching gaps. The methodology adopted for this purpose included bibliographic research, exploratory, based on Information Science and Computer Science areas, carried out through publications present in the ACM Digital Library and Google Scholar. Among the main results, we noticed the ontologies have been widely discussed in the literature and used in several proposals and experiments, providing significant improvements in the information retrieval process. Such resource enables the development of interactive features and functionality, semantic search, query expansion and refinement, as well as contributing to Semantic Web access projects, information visualization, multimedia retrieval, mobile devices and interface and system development. However, in spite of the numerous contributions, we suggest that ontologies should be used to enhance search by exploring the existing meaning between related concepts.
UTILIZAÇÃO DE ONTOLOGIAS NA RECUPERAÇÃO DE INFORMAÇÃO: principais abordagens, problemas e propostas de melhorias
Keywords: Information Retrieval; Information Visualization; Ontology; Search Interfaces; Semantic Search